Relationship between Deformation and Epigenetic Configuration of Rock and Soil Bodies on Slopes - Lu, Yibing (International Journal of Natural Resources and Environmental Studies, 2026)
The development and evolution of slopes can often destroy construction buildings, interrupt traffic, block rivers, and threaten the safety of people and animals. Therefore, it is of great practical significance to study their formation and development process and to take preventive measures. However, the surface structure often covers up some real structural appearance, so it can correctly identify the surface structure and distinguish it from the real structural deformation. It has great practical significance for geological mapping, regional structural research, analysis of hydrological engineering geological conditions, seismic geological survey and deposit exploration and mining. This paper first introduces the basic types of slope deformation and destruction and the mechanism mode of slope failure, and finally discusses the relationship between slope deformation and epinal structure.